The Development of Social Forestry in Indonesia:: Policy Implementation Review, 2007-2019 - Andi Setyo Pambudi (Pusbindiklatren Bappenas, 2020)
The phenomenon of sustainable forest management failure in Indonesia faces the reality of incompatible economic, social, and environmental approaches. Conventional forest management always assumes that good forests are only managed by the government through concession permit policies to large capital owners that are top-down and accompanied by a minimum condition of community involvement, which should be a key factor. Learning from the experience, Indonesia began to see the concept of social forestry as one of the efforts in the progress of a more sustainable development. Social forestry positions that the party that feels the greatest success or failure from forest management is the community around the forest itself. Communities must obtain the greatest access and incentives to manage forestry businesses as a source of life while preventing damage. In recent years, the agrarian reform program through social forestry is a breakthrough government program that is becoming increasingly demanded by communities. The rights to manage their surrounding lands in accordance with ancestral local wisdom are expected to be able to answer economic and ecological challenges. This paper specifically presents the development of social forestry and its issues and recommendations in the context of national development in Indonesia. The ecological harmony between humans and nature is a consideration of the importance of social forestry as a program to be continuously supported by the government, as well as to prioritize economic aspects in the principle of sustainable development.